Social Isolation, Loneliness and Well-Being: The Impact of WeChat Use Intensity During the COVID-19 Pandemic in China - Li, Jianfeng; Zhou, Luyang; Van Der Heijden, Beatrice; Li, Shengxiao; Tao, Hong; Guo, Zhiwen (Frontiers in Psychology, 2021)
So far, there is a lack of research on the impact of WeChat use on social isolation, loneliness, and well-being. Using 1,805 online questionnaires, this study examined this phenomenon among Chinese self-quarantining residents during the lockdown period of the COVID-19 pandemic. The results showed that lockdown WeChat use intensity positively moderated the relationships between lockdown social isolation and lockdown social loneliness, and between lockdown social isolation and lockdown stress as well as between lockdown social isolation and lockdown life dissatisfaction through lockdown social loneliness, on the other hand. Moreover, we found that lockdown WeChat use intensity positively affects lockdown social loneliness, which, in turn (partially) mediates the effect of lockdown WeChat use intensity, on the one hand, and lockdown stress and lockdown life satisfaction, on the other hand. More specifically, lockdown WeChat use intensity can increase lockdown stress and decrease lockdown life satisfaction in a direct way, and in an indirect way, that is through lockdown social loneliness, as well. These findings indicate that online social interactions, which presumably are valued by many people who believe that these can compensate for the lack of offline social interactions, relieve their perceived stress (anxiety) in actual life, and make their lives better, are in fact endangering their mental health and life satisfaction during the COVID-19 lockdown period. Based on these findings, recommendations for future scholarly work and practical implications are delineated.